Fiscal Performance and Economic Growth: A Scientometric Mapping of Global Research - I Putu Reza Krisna Putra; Ni Putu Wiwin Setyari (Journal of International Conference Proceedings, 2025)
This study aims to map the intellectual landscape of scholarly publications on fiscal performance and economic growth from 1968 to 2025 using bibliometric analysis. The significance of this research lies in its attempt to consolidate fragmented literature, identify conceptual trends, and uncover knowledge gaps, particularly in the context of fiscal decentralization. A total of 1,522 scientific documents were retrieved from the Dimensions database and analyzed using VOSviewer through co-occurrence, citation, and bibliographic coupling techniques. The findings reveal an increasing trend in academic attention, especially in the last decade, with China and the United States dominating research productivity. Six major thematic clusters were identified, ranging from fiscal sustainability and macroeconomic performance to governance, inequality, and regional case studies. Influential institutions such as the World Bank and IMF emerged as central knowledge hubs. The study provides critical insights for guiding future research agendas in fiscal innovation and local economic development. It also emphasizes the importance of inclusive knowledge production and interdisciplinary collaboration for designing adaptive fiscal policy frameworks responsive to global and local economic dynamics.